CRUISING TOURISM: DIFFERENTIATION THROUGH THE CHARACTERISTICS OF CRUISING ROUTE - Seric, Neven; Rakusic, Katja (European Scientific Journal, ESJ, 2014)
The problem of the research is to evaluate the impact properties of cruising routes to its differentiation. Perceived characteristics of routes by the target clients are defining valuation of the service, and the resolving dilemma for prices. The subject is the evaluating determinants of the cruising route’s characteristics (functional, social, and emotional). Cruising product is no longer selected primarily for the cruising service, but for the content of cruising route. The approach called “the land sea cruising in product development” is increasingly becoming an area of interest. The authors want to determine the affirmative characteristics that contribute the perception of cruising route. The main objectives of research were: determining the direction of the effects of the individual cruising route characteristics on service value’s perception, and providing an evaluation model of the route’s characteristics, explaining the cruising product value’s perception, and indicating significance variables of attraction. The following questions are offered to answer: What factors of cruising tourism are determining the value’s perception for a guest in the selection of cruising route; What are the determinants of cruising routes that prospective customers consider when assessing its value; How does each of the identified determinants affect the overall perceived value of the cruise route; How the overall perceived value of the cruise route affects customer behavior intentions. Based on the research work, authors have offered a new evaluation model of the cruising route differentiation, which represents a contribution to the research.